2018
DOI: 10.1002/cam4.1388
|View full text |Cite
|
Sign up to set email alerts
|

An open‐label, dose‐ranging study of Rolontis, a novel long‐acting myeloid growth factor, in breast cancer

Abstract: This randomized, open‐label, active‐controlled study investigated the safety and efficacy of three doses of Rolontis (eflapegrastim), a novel, long‐acting myeloid growth factor, versus pegfilgrastim in breast cancer patients being treated with docetaxel and cyclophosphamide (TC). The primary efficacy endpoint was duration of severe neutropenia (DSN) during the first cycle of treatment. Patients who were candidates for adjuvant/neoadjuvant TC chemotherapy were eligible for participation. TC was administered on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…Demographics of the 643 patients enrolled in the 2 phase 3 studies are summarized in Table 1. Similar demographics were observed in the phase 2 dose‐ranging study 11 …”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Demographics of the 643 patients enrolled in the 2 phase 3 studies are summarized in Table 1. Similar demographics were observed in the phase 2 dose‐ranging study 11 …”
Section: Resultssupporting
confidence: 63%
“…A phase 2 study, wherein eflapegrastim doses of 45, 135, or 270 μg/kg were compared with pegfilgrastim (6 mg), was performed to determine the optimal dose of eflapegrastim for evaluation in phase 3 clinical studies 11 . In this dose‐finding study, eflapegrastim produced a dose‐dependent increase in neutrophil counts after subcutaneous administration.…”
mentioning
confidence: 99%
“…4 Eflapegrastim shows increased uptake to the bone marrow, presumably due to the interaction of its Fc fragment with Fc receptors (FcRn) on the vascular endothelial surface. 5 The resulting increased potency, as demonstrated by pharmacokinetic and pharmacodynamic data from preclinical and Phase 1 and 2 studies, [5][6][7] gives eflapegrastim the potential to have an improved therapeutic index compared to pegfilgrastim. In nonclinical primate and rat studies, eflapegrastim demonstrated greater biologic activity than pegfilgrastim at reducing neutropenia, at one-third the G-CSF dose of pegfilgrastim.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Here we report the results of a second pivotal Phase 3 randomized study comparing eflapegrastim to pegfilgrastim (RECOVER, NCT02953340) in patients with Stage I to IIIA early-stage breast cancer (ESBC) undergoing standard docetaxel/cyclophosphamide (TC) therapy, which demonstrates confirmatory, reproducible evidence from another nearly identically designed, independent study (ADVANCE, NCT02643420) conducted in the same patient population. In contrast to Phase 1 and 2 eflapegrastim studies using weightbased dosing, 6,7 this Phase 3 study tested a fixed dose of 13.2 mg eflapegrastim (3.6 mg G-CSF) that is equivalent to 60% of the 6 mg G-CSF in pegfilgrastim. The 13.2 mg dose is equivalent to 188 µg/kg eflapegrastim (51 µg/kg G-CSF) for a 70 kg person and was chosen based on the results of a Phase 2 dose-ranging study, which showed noninferiority of eflapegrastim vs pegfilgrastim in the primary endpoint, mean Cycle 1 duration of severe neutropenia (DSN), for eflapegrastim 135 µg/kg (37 µg/kg G-CSF) (0.44 vs. 0.31 days, P = .002), and statistical superiority at 270 µg/kg (74 µg/kg G-CSF) (0.03 vs. 0.31 days, P = .023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation